1991
DOI: 10.1073/pnas.88.24.11037
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic field tomography of coherent thalamocortical 40-Hz oscillations in humans.

Abstract: This paper introduces the use of magnetic field tomography (MFT), a noninvasive technique based on distributed source analysis of magnetoencephalography data, which makes possible the three-dimensional reconstruction of dynamic brain activity in humans. MFE has a temporal resolution better than 1 msec and a spatial accuracy of 2-5 mm at the cortical level, which deteriorates to 1-3 cm at depths of 6 cm or more. MFT is used here to visualize the origin of a spatiotemporally organized pattern of coherent 40-Hz e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

19
316
2
1

Year Published

1993
1993
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 495 publications
(342 citation statements)
references
References 18 publications
19
316
2
1
Order By: Relevance
“…(3) A separate but related possibility is that proposed by Llinas and Ribary (Ribary et al, 1991;Joliot et al, 1994;Llinas et al, 1998). These authors propose that a thalamic pacemaker, driven by the intrinsic properties of the ionic conductances in various kinds of thalamic cell and modified by sensory input, may be responsible for the coherence of 40-Hz cortical rhythms they observe.…”
Section: Possible Mechanisms Of Generation Of Global Synchronymentioning
confidence: 99%
“…(3) A separate but related possibility is that proposed by Llinas and Ribary (Ribary et al, 1991;Joliot et al, 1994;Llinas et al, 1998). These authors propose that a thalamic pacemaker, driven by the intrinsic properties of the ionic conductances in various kinds of thalamic cell and modified by sensory input, may be responsible for the coherence of 40-Hz cortical rhythms they observe.…”
Section: Possible Mechanisms Of Generation Of Global Synchronymentioning
confidence: 99%
“…A color or gray level scale is then used to represent the square of the modulus of the current density at each point in the image. This technique is known as Magnetic Field Tomography (MFT), and was first applied to real data in the 3D reconstruction of a possible 40Hz thalamo-cortical interaction (Ribary et al 1991). A range of appropriate graphical representations for displaying the spatial form and dynamic evolution of these MFT solutions have been developed (Singh 1991;Singh et al 1991).…”
Section: The Current Dipole and Magnetic Field Tomographymentioning
confidence: 99%
“…Twodimensional source space models have been employed to study cortical activity for a number of evoked MEG signals (Ioannides et al 1990b). Three dimensional reconstructions have been performed for a variety of MEG signals, including 40 Hz steady state response from normal subjects and Alzheimer's patients (Ribary et al 1991), and interictal epileptic activity (Ioannides et al 1993).…”
Section: The Current Dipole and Magnetic Field Tomographymentioning
confidence: 99%
“…EP analysis based on systems theory rules and application of digital filters also showed that a marked 40-Hz component follows stimulation (Başar, Rosen, Başar-Eroglu, & Greitschus, 1987). For further studies of evoked electric and magnetic 40-Hz activity see, e.g., Galambos, Makeig, & Talmachoff (1981), Pantev et al (1991), and Ribary et al (1992). A large number of studies at the single-cell level complement these results (Llinás, 1988;Gray & Singer, 1987;Gray, König, Engel, & Singer, 1989;Eckhorn et al, 1988).…”
Section: Discussionmentioning
confidence: 88%